PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ45 DI BURSA EFEK INDONESIA TAHUN 2017-2021 - Raharjo, Stiyo Pamungkas; Sari, Lita Permata; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The company began to change its business strategy which was initially based on labor (labor based business) to a business based on knowledge (knowledge based business) as an actualization of one form of intangible assets (intangible assets). Intellectual capital provides added value to the company. If the company has Intellectual capital with good governance, it will have an impact on the company's market value. The purpose of this study is to analyze and test the Influence of Intellectual Capital on company Value through financial performance. This research uses quantitative research methods. The population in the study were companies listed in the LQ45 Index with a sample of 9 companies. The sampling technique uses purposive sampling technique . Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Intellectual capital has a significant positive effect on financial performance, Intellectual capital has a positive but not significant effect on company value, financial performance has a significant positive effect on financial performance The value of the company. The results of the hypothesis test of indirect influence show that the intellectual capital variable on the company's value through financial performance has a positive but not significant effect.